Factors affecting mountain biking demand at Putrajaya Challenge Park - Che Ibrahim, Nur Syuhada; Mohammad Afandi, Syamsul Herman; Samdin, Zaiton (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Mountain Biking (MTB) is becoming increasingly popular in Malaysia. With growing demand, more cycling sites are needed and specially organised events for MTB were encouraged by the Malaysian government in conjunction with efforts at encouraging wider participation among the public in active sports and recreation for a healthy lifestyle. One of the results of this effort is the establishment of the Putrajaya Challenge Park (PCP). As a sport, MTB is known to be associated with risks and requires high technical skills. The purpose of this study is to determine the factors affecting in MTB participation and demand at PCP. Data was collected using a structured questionnaire. A multiple linear regression analysis suggested that three factors were significant at the p < 0.05 probability level - total travel cost, years of participation and cost of equipment upgrade.